A Mission Assurance Framework for R&D Organizations. Issue 1 (13th September 2016) - Hahn, Heidi Ann
Abstract: Research and development (R&D) organizations such as the National Nuclear Security Administration's national security laboratories span a spectrum of R&D from basic scientific research to demonstration of actual system prototypes in an operational environment. Application of systems engineering (SE), engineering quality and rigor, and project management is often critical to successful R&D outcomes, but a graded approach is key – neither the type of project being performed nor the funding profile provided by the customer may support the application of very formal processes. To address these challenges, the Los Alamos National Laboratory (LANL) has developed and is implementing a Mission Assurance Framework that applies the concepts of systems engineering, project management, and engineering quality and rigor using a risk‐based graded approach. This paper describes the LANL approach to developing and implementing the Mission Assurance Framework and discusses the policies, tools, and training that support the diverse set of projects performed across the Laboratory's mission space. Emphasis is placed on the SE and engineering quality aspects of the Framework.